Plan of solid waste management ofbatteries for a telephony sector company - Mesquita, Glaucia Machado; Souza, Marco Aurélio Pessoa-de-; Silva, Aline Cândida da; Rabelo, Alexandre (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The uncontrolled growth and often without strategic planning environmental control forces the market for becoming increasingly demanding in there environmental quality companies. This fact demands not only offering quality products, but also the implementation of a responsible administration that worry so much about the social aspect as to the environmental. The solid waste management plan (SWMP) of batteries aims to meet the environmental and public health requirements as existing laws, based on the principles of non-generation and minimization of waste generation, pointing and describe the actions related to their management, covering all aspects related to reduction of waste production, reuse, separation, packaging, and also undertakes to manage their solid waste. This study is presenting the solid waste management plan (PMSW) of the telephone company, the problems involving the disposal or improper handling of batteries. The company develops technical criteria that lead to minimizing the risk to public health and the environment as well as work safety standards in the company.